Kinerja Manajemen Rantai Pasok Sayuran di Griya Hijau Hidroponik - Naomy, Seisha Putri; Renaldi, Eddy (Universitas Galuh, 2025)
Griya Hijau Hidroponik is a hub that integrates two main sources: internal production and supply from supplier partners to meet market demand. There are issues in meeting market demand due to the limited volume of vegetables, resulting in low service levels at certain market destinations. This study aims to analyze the supply chain structure and measure the supply chain management performance of vegetables at Griya Hijau Hidroponik. The object of this research is the supply chain management performance of vegetables, which is measured using the Supply Chain Operations Reference (SCOR) Model Version 12.0. The research method used is qualitative with a descriptive approach and a case study design. The vegetable supply chain structure is classified as part of the fresh food supply chain. There are two supply chain structures: the supply chain structure for the market destination of Restaurant A, which falls under the direct supply chain, and the supply chain structure for the market destination of Restaurant B, which is part of the extended supply chain. The measurement results for each indicator show the following performance: Perfect Order Fulfillment (96% - Excellent), Order Fulfillment Cycle Time (100% - Excellent), Upside Supply Chain Adaptability (60% - Average), Cost of Goods Sold (71% - Good), and Cash to Cash Cycle Time (100% - Excellent). Overall, the supply chain management performance of vegetables at Griya Hijau Hidroponik is categorized as